Boundary element method based algorithm for simulation of fluid flow in 3D - Ravnik, Jure; Škerget, Leopold (Proceedings in applied mathematics and mechanics, 2011)
A boundary element method based numerical scheme that solves the velocity‐vorticity formulation of Navier‐Stokes equation is presented. The developed method is validated and used to simulate laminar viscous flow coupled with heat transfer in 3D. Benchmark test cases were use to determine the validity of the method. Flow around a hotstrip is presented as a test case. (© 2011 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)